The Teaching Model and Basic Religious Texts Prepared by Jesuits Working in Lithuania and Poland from the 2nd half of the 16th c. to the 1st half of the 17th c. - Łukaszewska-Haberkowa, Justyna (Vilnius University Open Series, 2021)
The article shortly describes the model of teaching and basic religious texts written in Lithuanian in the 2nd half of the 16th c. and in the first half of the 17th c. by Jesuits in the Polish-Lithuanian Commonwealth. The fundamental goal of the Jesuit Society was to spread the Christian faith. To this aim the best and most effective methods were utilised. In the described period two forms of education coexisted, namely the system of schools and pastoral work within the society. While the former focussed on teaching Latin, the latter contributed to the development and codification of vernaculars, and specifically Lithuanian. Good understanding and established social relations were the objective of Jesuits. Pastoral work in a way preceded ethnolinguistic studies. Only those priests and brothers were selected for work with people who knew the language, at least to some extent. The knowledge of Latin was regarded as obvious. The teaching of languages in the spoken and written form was first based on the skills of individual brothers, but after a certain time a seminar devoted to the languages of the Commonwealth was founded. As the time passed and the Lithuanian Province developed, more attention was payed to the culture and development of the language. It was commonly used in apostolic work – in sermons, liturgical texts and pious literature throughout Lithuania. The teaching model applied by Jesuits also contributed, albeit indirectly, to the development of the Lithuanian language and culture.